Selenium-enriched oolong tea (Camellia sinensis) extract exerts anti-inflammatory potential via targeting NF-κB and MAPK pathways in macrophages - Qi Wang; Juqing Huang; Yafeng Zheng; Xuefang Guan; Chenchun Lai; Huiying Gao; Chi-Tang Ho; Bin Lin (Food Science and Human Wellness)
ABSTRACT: Both tea polyphenols and selenium (Se) have been suggested to exert the health benefits via the regulatory capacities of chronic inflammation, which make Se-enriched oolong tea a promising beverage as an anti-inflammatory diet. The aim of this study is to investigate the anti-inflammatory effects of Se-enriched oolong tea extract (Se-TE) and underlying mechanism in lipopolysaccharide (LPS)-induced RAW264.7 cells. Se-TE treatments (50 and 150 μg/mL) significantly suppressed the over-production of nitric oxide (NO) and prostaglandin E2 (PGE2) in LPS-stimulated macrophages via downregulating the expression of nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2). Moreover, Se-TEs also effectively inhibited the productions of inflammatory cytokines, such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β). Furthermore, Se-TE could block mitogen-activated protein kinase (MAPK) and nuclear factor-kappa B (NF-κB) signaling pathways through the inhibition of the phosphorylation of key proteins (IκB-α, p65, p38, ERK, and JNK) and the translocation of the p65 subunit into the nucleus. Collectively, our results indicated that Se-TE may have the potential to be used as a novel food ingredient for the development of various anti-inflammatory foods and the treatment and prevention of chronic inflammation-related diseases.